The evaluation of internal communication systems A method for the comprehension of communication in organizations: Un método para la comprensión de la comunicación en las organizaciones - Hernández García, David (Folios, revista de la Facultad de Comunicaciones y Filología, 2018)
This paper reviews the conceptualization of communication in organizations and proposes bases for a comprehensive understanding of internal communication systems in an organization from a diagnosys basis. As a basis for comprehension we propose that the internal communication system is composed by the set of practices and proceedings established by the organization to exchange information, make consultations and transmit orders to employees regarding objectives of different leves, through different channels and directions.